A Critical Review: Spinning Methodologies, Properties and Applications of Graphene Fibre (Journal of Fiber Bioengineering and Informatics, 2018)
Inspired by macroscopic high dimensional graphene materials, graphene fibres now have been fabricatedin a range of methods, including drawing, solution spinning, thermal process, electrospinning, etc.Among them, most attractive, large-scale and widely used methodology is solution spinning liquidcrystal graphene oxide, including wet spinning and dry-jet wet spinning. Properties of diRerent kinds ofgraphene fibres were discussed in this review. Both neat graphene fibres and hybrid graphene fibres showremarkable mechanical and electrical properties, actuating properties and flexibility. Multifunctionalproperties provide graphene fibres potential in functional textiles, flexible and wearable sensors,supercapacitors, electrodes of supercapacitors, energy devices, and actuators etc. It is prospected thatproperties of graphene fibres will be further optimized, and their application will be more realistic andwell developed.
Keywords: Graphene Fibres; Spinning; Mechanical Properties; Electrical Properties; Application